2021
DOI: 10.1016/j.encep.2020.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased in-hospital mortality from COVID-19 in patients with schizophrenia

Abstract: Background There is limited information describing the presenting characteristics and outcomes of patients with schizophrenia (SCZ) requiring hospitalization for coronavirus disease 2019 (COVID-19). Aims We aimed to compare the clinical characteristics and outcomes of COVID-19 SCZ patients with those of non-SCZ patients. Method This was a case-control study of COVID-19 patients admitted to 4 AP–HM/AMU acute care hospitals in Marseille, southe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
1
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 16 publications
5
46
1
9
Order By: Relevance
“… 16 Previous studies have also demonstrated a pattern of higher IHD mortality, yet lower or no increased risk of IHD in schizophrenia, 16 , 30 a finding that has been suggested to be associated with lower help-seeking behavior. 31–33 The higher rates of mortality also confirm the results reported by Fond et al, 10 who found a significantly higher prevalence of schizophrenia diagnoses among individuals admitted to acute care hospitals in France. Previous studies have indicated that aside from baseline physical comorbid illnesses, schizophrenia patients engage in smoking behavior more frequently and are therefore more vulnerable to smoking-related illnesses such as COPD, 16 which is considered a risk factor for COVID-19 mortality.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“… 16 Previous studies have also demonstrated a pattern of higher IHD mortality, yet lower or no increased risk of IHD in schizophrenia, 16 , 30 a finding that has been suggested to be associated with lower help-seeking behavior. 31–33 The higher rates of mortality also confirm the results reported by Fond et al, 10 who found a significantly higher prevalence of schizophrenia diagnoses among individuals admitted to acute care hospitals in France. Previous studies have indicated that aside from baseline physical comorbid illnesses, schizophrenia patients engage in smoking behavior more frequently and are therefore more vulnerable to smoking-related illnesses such as COPD, 16 which is considered a risk factor for COVID-19 mortality.…”
Section: Discussionsupporting
confidence: 84%
“…Reilev et al 9 performed a population-based study to assess factors that might contribute to a higher risk of severe and fatal COVID-19 disease among Danish individuals, and found that a major psychiatric disorder increased the odds of mortality by 2.4–2.7. To the best of our knowledge, only one study has assessed the association between schizophrenia diagnosis and severity of COVID-19 illness: Fond et al 10 performed a case-control study of 1092 patients admitted to acute care hospitals due to COVID-19 illness in Marseille, France, and found increased mortality rates among patients with schizophrenia (26.7%) compared to patients without schizophrenia (8.7%). Nonetheless, the authors stated that the sample of schizophrenia patients included only 15 cases, and the database suffered from missing data and potential inaccuracies, precluding strong conclusions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those suffering from schizophrenic psychoses are not just more likely to contract COVID-19, they are more likely to die from it; they are more likely to experience a deterioration of their psychiatric symptoms, and they are more likely to misperceive risk and fail to adopt protective measures [ 25 , 26 , 27 ]. They are particularly vulnerable to the consequences of the pandemic, and rather than have their care funding reduced and redirected to managing COVID-19, they should instead receive increased support.…”
Section: Effect Of Covid-19 On People Who Use Psychiatric Servicesmentioning
confidence: 99%
“…1 ). Initial reports described increased risk for mortality in hospitalized COVID-19 patients with schizophrenia [ 2 , 3 ]. This phenomenon was attributed to the lack of adherence to public health measures (social distancing, hand washing, and the use of face masks) by patients, the limited availability of health services for patients with mental disease because of hospital saturations, or the delayed medical attention or treatment-seeking.…”
mentioning
confidence: 99%